VULVA HYGIENE AWARENESS TO CHANGES IN KNOWLEDGE, ATTITUDE AND BEHAVIOR OF TEENAGE STUDENTS - Daniel Ardian Soeselo; Farren Oktavia Suhardi; Garry Grimaldy; Felicia Kurniawan; Nelly Tina Widjaja; Sandy Theresia; Sanny Winardi (Jambura Journal of Health Sciences and Research, 2021)
Maturation of female reproductive organs begins in adolescence. Education about vulvar hygiene is one of the efforts to improve the health of reproductive organs. The purpose of the study was to determine the level of knowledge and changes in attitudes and behavior of adolescent students towards vulva hygiene after receiving education about vulvar hygiene. The research method was pre-test and post-test using a questionnaire, a sample of 83 respondents through the inclusion criteria. Education about vulvar hygiene was given after the pre-test. The post-test was conducted immediately after the educational session and repeated one month later. The results of the study, the mean value of the pre-test regarding knowledge, attitudes, and behavior was 13.87; 16.57; and 4.78. The mean value of the post-test one month later regarding knowledge, attitudes, and behavior was 26.87; 44.90; and 12.53. Paired T-test on knowledge, attitudes, and behavior showed a p-value of 0.000; 0.000; and 0.000. Conclusion: It was found that the value of knowledge, attitude, and behavior was low before being given education about vulvar hygiene. There was a significant change in value after providing education about vulvar hygiene. This shows the importance of education about vulvar hygiene in adolescent students. Keywords: Vulvar Hygiene, Knowledge, Adolescent